Pengaruh Nilai Tukar dan Debt to Equity Ratio terhadap Harga Saham pada Industri Makanan dan Minuman di Indonesia - Astri Astri; Nafsa Qolbina Istigfari; Syahla Nur Fikriyyah; Sintia Anggraeni; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study aims to analyze the effect of the exchange rate (KURS) and the Debt to Equity Ratio (DER) on stock prices in food and beverage subsector companies in Indonesia. Using panel data for the 2021-2024 period using the Random Effects Model (REM) method, this study aims to demonstrate the partial and simultaneous effects of these two independent variables. The results show that the KURS has a positive and significant effect on stock prices, while the DER has no significant effect partially. However, the results indicate that simultaneously, the KURS and DER have a significant effect on stock prices, with an R-squared value of 16,56%, indicating that most of the stock price variation is explained by factors other than the model. This finding emphasizes the importance of exchange rate stability for capital market performance and suggests that leverage structure is not a primary determinant in investor assessments in the food and beverage subsector.